Metody fizykalne w terapii odleżyn = Physical methods for the treatment of bedsores - Agnieszka Radzimińska; Dorota Stettler; Magdalena Weber-Rajek; Agnieszka Anna Zimmermann; Krzysztof Sowała; Aleksander Goch; Walery Zukow (Kazimierz Wielki University, 2015)
Radzimińska Agnieszka, Stettler Dorota, Weber-Rajek Magdalena, Zimmermann Agnieszka Anna, Sowała Krzysztof, Goch Aleksander, Zukow Walery. Metody fizykalne w terapii odleżyn = Physical methods for the treatment of bedsores. Journal of Education, Health and Sport. 2015;5(4):405-414. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.38244 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%284%29%3A405-414 https://pbn.nauka.gov.pl/works/685685 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.03.2015. Revised 05.04.2015. Accepted: 26.04.2015.   Metody fizykalne w terapii odleżyn Physical methods for the treatment of bedsores   Agnieszka Radzimińska1, Dorota Stettler2, Magdalena Weber-Rajek1, Agnieszka Anna Zimmermann3, Krzysztof Sowała4, Aleksander Goch1, Walery Zukow5   • 1.      Uniwersytet Mikołaja Kopernika w Toruniu, Collegium Medicum w Bydgoszczy, Katedra Fizjoterapii, Bydgoszcz, Polska • 2.      Bydgoska Szkoła Wyższa, Bydgoszcz, Polska • 3.      Wyższa Szkoła Gospodarki, Bydgoszcz, Polska • 4.      Szpital Polski, Sztum, Polska • 5.      Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Bydgoszcz, Polska   Adres do korespondencji: dr n. med. Agnieszka Radzimińska Uniwersytet Mikołaja Kopernika w Toruniu Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy Katedra Fizjoterapii ul. Marii Skłodowskiej-Curie 9, 85-094 Bydgoszcz e-mail: agnieszka.radziminska@gmail.com   Streszczenie Odleżyny (obok zakażeń szpitalnych) to najpoważniejsze powikłania występujące u pacjentów hospitalizowanych. Od lat poszukuje się najskuteczniejszych metod leczenia zachowawczego odleżyn. Wśród tych metod należy zwrócić uwagę na metody leczenia fizykalnego, a wśród nich: fototerapię, elektroterapię, magnetoterapię i sonoterapię.   Summary Pressure ulcers (next to nosocomial infections) are the most serious complications occurring in hospitalized patients. For years he sought the most effective methods of conservative treatment of pressure ulcers. Among these methods, you must pay attention to the methods of physical treatment, among them: phototherapy, electrotherapy, magnetic fields and sonotherapy.   Słowa kluczowe: metody fizykalne; terapia; odleżyny. Keywords: physical methods; therapy; bedsores.